Isolasi dan Identifikasi Bakteri pada Ikan Kerapu Lumpur (Epinephelus coioides) yang Dibudidayakan di Keramba Jaring Apung Kota Lhokseumawe - Anis Nugrahawati; Akmal Izwar; Elfiana Elfiana; Rossy Azhar; Dani Pratama Putra; Syahirman Hakim (Jurnal Sains Pertanian, 2025)
Bacterial diseases are among the major factors limiting the productivity of mud grouper (Epinephelus coioides) aquaculture. This study aimed to isolate and identify bacteria from the kidney, gills, and skin mucus of mud grouper cultured in floating net cages in Lhokseumawe, Aceh, Indonesia. The study was conducted from August to September 2024 using an observational method combined with laboratory-based analysis. A total of ten fish (approximately 20 cm in length) showing clinical signs of bacterial infection, including lethargy, erythema, and hemorrhage, were selected using purposive sampling. Bacterial isolation was performed on 3% Tryptic Soy Agar (TSA) and incubated at 26–30°C for 24 h. The isolates were identified using the Analytical Profile Index (API) Kit. The results revealed the presence of Vibrio alginolyticus, Vibrio harveyi, Streptococcus iniae, and Bacillus cereus. Vibrio alginolyticus and Vibrio harveyi were isolated from the kidney and gills, whereas Streptococcus iniae was detected in the gills and skin mucus. Bacillus cereus was identified only from the skin mucus. These findings provide baseline information on bacterial diversity associated with cultured mud grouper and may support disease diagnosis and fish health management in floating net cage aquaculture.